CASCARA PRODUCTIONS AS A MODEL OF BRAND ACTIVISM FOR COFFEE FARMER GROUP IN MOUNT PUNTANG, WEST JAVA INDONESIA - Siswantini, Siswantini; Sumbogo, Tri Adi; Dhamayanti, Meilani; Maryani, Maryani (SEEIJ (Social Economics and Ecology International Journal), 2025)
Cascara is considered a healthy drink and one way to encourage sustainable coffee production by-products. Cascara production activities by the Rumah Kopi Palalangon can be categorized as brand activism, namely a brand that uses activist strategies with the desire to improve the quality of life of the community. The essence of brand activism is action that involves all stakeholders to make changes in social, economic, political and environmental quality. This research aims to develop a basic training plan for empowering farmers who are members of the rumah Kopi Palalangon led by Ayi Suteja in Mount Puntang, Bandung Regency, West Java. This research focuses on creating messages on social media that have been used as promotional media for their activities. CBR approach usages to identify the partner’s need and follow the ABCD approach to capture the potential social capital that exists in the community. As activists, PKM partners are trying to spread their activities in producing coffee with a zero-waste concept. The study shows that partners lack the ability to provide a clear message of the movement that could motivate the audience to participate. Based on their social and material assets, a training plan of a psychology of message and brand activism strategies is developed and implemented.